Beyond the Timeline: Constructing time and age identities on Facebook. (September 2015) - Georgalou, Mariza
Abstract: Human actions and activities take place on some timescale (Lemke, 2000 ). Within the context of Facebook, all kinds of material posted on one׳s profile, be that photos, stories and experiences, are organised in the form of a Timeline with time-stamps being appended automatically. Yet, the sense of identity linked to time is actively constructed in the posts, and is done in interaction with other people. Viewing time as a polysemous entity (Evans, 2005 ) and as a significant orientation device for the self (Georgakopoulou, 2003 ), this paper examines the ways in which Facebook users position themselves in time as well as the different ways in which they conceive and value age. Drawing on insights from discourse-centred online ethnography (Androutsopoulos, 2008 ), the frameworks of age-categorisation and temporal framing on identity marking (Coupland et al., 1991 ) and research on small stories (Georgakopoulou, 2007; Page, 2010 ), I present and discuss empirical data from a Greek female user׳s Timeline. Focusing on instances of explicit and implicit references to age and ageing, I argue that age identity is an interactive and collaborative process both facilitated and hindered by certain Facebook configurations. The findings also show that Facebook can be divorced from its orientation to the present as participants utilise the medium to evoke certain periods of life, recycle memories, appeal to experiences and recall past tastes. Highlights: The construction of age identity is relative and relational. Time and age identity construction is an interactive and collaborative task. Time and age identity co-constructions hinge upon Facebook affordances. Facebook can be divorced from its orientation to the present moment. Participants utilise Facebook to evoke the past and recycle memories.